Collaborative playwriting : polyvocal approaches from the EU Collective Plays project - Castagno, Paul C., 1950- (Routledge, Taylor & Francis Group, 2020)
"In Collaborative Playwriting, five collectively-written plays apply polyvocal methods in which clash and frisson replace synthesis, a dialogic approach to collective writing that has never before been articulated or documented. Based on the EU Collective Plays Project, this collection of plays showcases each voice is in dialogic tension and relation to the other voices of the text, offering an entirely novel approach to new play development that challenges the single (and privileged) authorial voice. Castagno's case study approach provides detailed commentary to each of the various experimental methods, exploring the plays' processes in detail. The book offers an evolutionary path forward in how to develop new work, thus encouraging and promoting the writing of collective, hybrid plays as having profound benefits for all playwrights. The ground-breaking approaches to playmaking in Collaborative Playwriting will appeal to playwriting programs, instructors, academics, professional playwrights, theatres, new play development programs; as well as courses in gender LGBTQ studies, script analysis, dramaturgy, dramatic literature--across the theatre studies curricula"--